PENERAPAN EVIDENCE BASED NURSING : Pengaruh Pemberian Oral Hygiene Menggunakan Chlorhexidine 0,2% Dengan Teknik Toothbrush Terhadap Kesehatan Mulut Pada Pasien Yang Terpasang Ventilasi Mekanik Di Ruang ICU - Indah Burdah Sari (2022)
Background: Oral hygiene using 0.2% chlorhexidine solution with the toothbrush technique in mechanically ventilated patients can improve oral hygiene and reduce the risk of VAP. Objective: To determine the effect of oral hygiene using 0.2% chlorhexidine with toothbrushes in ventilated patients. mechanics with the oral hygiene of patients in the ICU. Methods: To measure the level of oral hygiene of patients in the ICU using the BOAS index approach (Beck Oral Assessment) Results: The results of the case study showed a decrease in the BOAS value from the application of oral hygiene using chlorhexidine 0.2% in patients who were mechanically ventilated and given nursing actions for three days of implementation. Keywords: Chlorhexidine 0,2%, Mechanical Ventilation, Oral Hygiene, Toothache.